RESEARCH OF ETHNO-SPECIFICS OF HUNGARIAN NATIONAL COSTUME FOR DESIGNING MODERN WOMEN CLOTHES - Білей-Рубан, Н. В.; Сєдоухова, Є. В.; Козманко, Г. Й. (Art and Design, 2018)
Analysis of constructive and decorative features of the Hungarian folk costume in the process of designing actual women's collection of clothing for everyday purposes. For the analysis of literary sources was used the historical analysis of scientific works on the study of the features formation of the Hungarian national costume. The research has been conducted using visual - analytical method for the study of ethnic features of Hungarian costume, its ornamentation, coloring and decoration; the association method, styling method, combinatorial method – for the transformation of the constructive and decorative characteristics of the Hungarian costume into the principles of designing modern women's clothing; methods of technical modeling - for the development of a collection of clothing. Results. The characteristics of the investigated creative source for transformation into the principles of designing women's clothes are obtained. The types of construction of women's clothing based on Hungarian folk costume, ornamentation and decoration are determined. Scientific novelty. The rational approaches to the principles of artistic creating of modern women's clothes are presented according to the structural and decorative features of the national costume of Sobolech-Sotmar of Berezsky region (Hungary).